Achieving Therapeutic Success with Spesolimab: Two Cases of Drug-Induced Generalized Pustular Psoriasis Initially Mimicking Acute Generalized Exanthematous Pustulosis - Chen J; Xia Y; Zhou F; Tao J; Zhou N (Journal of Inflammation Research, 2025)
Jianxia Chen,1,* Yuting Xia,2,3,* Faqiong Zhou,1 Juan Tao,2,3 Nuoya Zhou2,3 1Department of Dermatology, The Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Enshi, Hubei, People’s Republic of China; 2Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Hubei Engineering Research Center of Skin Disease Theranostics and Health, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nuoya Zhou, Department of Dermatology, Union Hospital, Tongji Medical College, No. 1277 Jiefang Avenue, Wuhan, Hubei, 430022, People’s Republic of China, Email zny2017@hust.edu.cnBackground: Patients with newly diagnosed generalized pustular psoriasis (GPP) lacking a history of psoriasis but with recent medication exposure may present with clinical features overlapping with acute generalized exanthematous pustulosis (AGEP). Accurate differentiation is critical for treatment and prognosis.Case Summary: We report two cases of drug-induced GPP initially with AGEP-like manifestations. Both patients received systemic glucocorticoids and cyclosporine yet exhibited recurrent pustular flares with lakes of pus and a prolonged disease course exceeding two months. Genetic testing confirmed IL36RN mutations in both cases. Subsequent spesolimab therapy achieved rapid resolution of pustules and sustained remission.Conclusion: In patients with first-onset drug-induced pustulosis resembling AGEP, the presence of lakes of pus, prolonged duration, and recurrent flares despite conventional therapies should be diagnosed as GPP promptly. Early intervention with spesolimab demonstrates efficacy in controlling disease activity and improving outcomes.Keywords: generalized pustular psoriasis, acute generalized exanthematous pustulosis, IL36RN gene, spesolimab